Development of Interactive-Based Learning Modules on Main Idea Material to Improve Reading Comprehension Skills of Grade IV Elementary School Students - Pipi Andriani; Mardianto; Pangulu Abdul Karim (Yayasan Zia Salsabila, 2025)
The purpose of this study is to develop a valid, practical, and effective interactive learning module in the main idea material. The type of research conducted is development research or commonly known as Research and Development (R&D). This research methodology uses the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The population of this study was 20 fourth-grade students. Data collection instruments in the study used validation sheets, questionnaires, and tests. Data collection techniques in the study were by testing the validity of two validators, testing the practicality, and testing the effectiveness using normalized values (N-Gain). The results of this study indicate that: (1) The interactive-based learning module was declared